STRATEGI BAURAN PEMASARAN RUJAK HOUSE PEKANBARU DALAM MENINGKATKAN DAYA TARIK PELANGGAN - Aprianda, Yogi; Yozani, Ringgo Eldapi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Marketing strategy is a directed and planned marketing effort to achieve optimal results. If this strategy is developed taking into account the marketing environment. Considering the possibilities in the food and beverage culinary industry today, many companies usually offer menus and flavors that are very attractive to culinary lovers. Rujak House Pekanbaru is a culinary delight with the sensation of enjoying food while playing with KOI fish. Offers the sensation of eating while accompanied by KOI fish. KOI fish are not placed in aquariums, but in ponds. This pool is filled with chairs and dining tables, where visitors can interact directly with KOI fish. Research shows that the strategy implemented by Rujak House Pekanbaru to increase customers is by using the 4P marketing mix strategy (produce, price, place, and promotion). Namely product, price, place and promotion strategies. The product strategy implemented is selling Apart from rujak, Rujak House also presents other typical Indonesian food menus such as meat soup, Balinese chicken satay wrap, grilled rice, fried chicken, fried rice, penyet chicken, and drinks such as orange ice, fruit salad, tamarillo juice and other types of juice, as well as the prices offered are affordable. And the promotion implemented is only using a word of mouth promotion strategy (personal selling strategy). Keywords: Marketing Mix, Rujak House, Customer Attraction